Comparisons of Glutamate in the Brains of Alzheimer’s Disease Mice Under Chemical Exchange Saturation Transfer Imaging Based on Machine Learning Analysis - Liu, Yixuan; Li, Jie; Ji, Hongfei; Zhuang, Jie (Frontiers in Neuroscience, 2022)
Chemical Exchange Saturation Transfer (CEST) is one of the cutting-edge molecular magnetic resonance imaging (MRI) technologies, which can indirectly measure low-concentration metabolites or free protein signals that are difficult to detect by conventional MRI technology. To apply CEST technology to Alzheimer’s disease, we obtained the corrected CEST data from the reference image of the water saturation spectrum, and performed analyses from both dimensions of ROIs and pixels. From the analysis of the ROI dimension, we found that the content of glutamate in the brain of AD mice is higher than in normal mice of the same age. In the analysis of the pixel dimension, we obtained the distribution map of glutamate in the mouse brain. For the experimental data in this study, we designed an algorithm framework based on data migration, using the Resnet neural network to classify the distribution of glutamic acid, and the accuracy rate can reach 76.5%. We evaluated the possibility of glutamate imaging as a biomarker for AD detection for the first time, and demonstrated its potential to characterize metabolic defects in specific areas of neurodegenerative diseases.